RANCANG BANGUN DAN UJI KINERJA HIGH VOLUME AIR SAMPLER UNTUK MENGUKUR TOTAL SUSPENDED PARTICULATE - Arief Sabdo Yuwono (Purifikasi, 2012)
Total suspended particulate (TSP) is fine particles in ambient air that settles very slowly and is normally measured using High Volume Air Sampler (HVAS). A HVAS should meet several design criteria, such as air flow rate of 1.13 to 1.70 m3/min according to national standard (SNI). This research produced ​​four HVAS units using different types of fan and air vacuum pumps, i.e. centrifugal fan, axial fan, vacuum pumps with the power of 600 Watt and 1000 Watt. During performance test, the highest flow rate in the order of 0,518 m3/min was produced by 1000 Watt vacuum pump HVAS. Comparison test between designed HVAS and the reference HVAS showed that the ambient TSP concentration was 60.3% of those measured by reference HVAS.